PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA (TINJAUAN PUTUSAN Nomor : 08/Pid.B/ 2013/PN.GS) - Yusfandi Zendrato Zendrato Vicky Qadosi Duha; Adrianus Amajihono Amajihono Amajihono (Ilmu Hukum Prima (IHP), 2019)
The crime of murder is planning a crime eliminates the life of another with a double a mature plan which can be caused by many factors such as economic conditions, social status, religion and others, where a criminal offence is including a criminal offence related to humanity. Accountability law against the perpetrators of the crime of murder was planned in accordance with article 340 of the book the laws of criminal law, namely in the form of criminal dead or in jail. In applying such article is inseparable from the rule or rules that apply in the law of criminal procedure so that created a system of conviction that can fulfill the purpose conviction itself. The overthrow of the criminal perpetrators of criminal acts against the assassination plan must be with the deliberations of judges such as the elements of a criminal offence which must be met, as well as evidence of the facts in the trial, so that the resulting verdict later can be accounted for.